PEMBERIAN KOMPRES DAUN KUBIS DINGIN MENGURANGI PEMBENGKAKAN PAYUDARA IBU POST PARTUM - Andari, Yuli; Sari, Dewi Yulia; Astriana, Astriana; Iqmy, Ledy Octaviani (Universitas Malahayati Bandar Lampung, 2021)
Background The highest percentage of exclusive breastfeeding coverage is in West Nusa Tenggara (87.35%), while the lowest percentage is in Papua (15.32%), while Lampung Province is in eleventh place with a percentage achievement of 64.98%. One of the things that can cause obstacles in exclusive breastfeeding is the presence of problems in the breast. One of the most common breast problems is breast milk dam or breast engorgement. Interventions to relieve the symptoms of breast engorgement are urgently needed. Strategies to reduce breast swelling non-pharmacologically can be done with acupuncture, traditional breast care (hot compresses combined with massage), cabbage leaves.The purpose of this study is to know the effect of giving cold cabbage leaf compresses to breast swelling of postpartum mothers in the Long Bandar Lampung Health Center Work Area in 2021.Methods This type of research is quantitative, the research design is pre-experimental method with a One group pretest – posttest design approach, the object of research is the effect of giving cold cabbage leaf compresses to breast swelling in postpartum mothers. Data analysis used univariate, bivariate t-test dependent.Result The average breast swelling of post partum mothers before being given cold cabbage compresses with a mean of 4.00 after being given cold cabbage compresses with a mean of 0.77.Conclusion it can be interpreted that there is an effect of giving cold cabbage leaf compresses to breast swelling of postpartum mothers in the work area of the Panjang Bandar Lampung Public Health Center in 2021.Suugestion It is expected that health workers in order to provide good counseling and information about the benefits of non-pharmacological treatment in dealing with the problem of breast engorgement in post partum mothers, especially for mothers with primiparas where these mothers do not understand correctly about how to breastfeed both for primiparous mothers to avoid the occurrence of breast milk dams.Keywords : Cold Cabbage Leaf Compress, Breast Swelling, Post Partum Mother ABSTRAKLatar Belakang Persentase tertinggi cakupan pemberian ASI eksklusif terdapat pada Nusa Tenggara Barat (87,35%), sedangkan persentase terendah terdapat pada Papua (15,32%), sedangkan Provinsi Lampung berada pada urutan ke sebelas dengan pencapaian persentase 64.98%. Salah satu hal yang dapat menyebabkan hambatan dalam pemberian ASI eksklusif adalah adanya permasalahan pada payudara. Salah satu permasalahan pada payudara yang sering terjadi adalah bendungan ASI atau pembengkakan payudara. Intervensi untuk meringankan gejala pembengkakan payudara sangat dibutuhkan. Strategi untuk mengurangi pembengkakan payudara secara non farmakologis dapat dilakukan dengan akupuntur, perawatan payudara tradisional (kompres panas dikombinasikan dengan pijatan), daun kubis. Tujuan penlitian ini diketahui pengaruh pemberian kompres daun kubis dingin terhadap pembengkakan payudara ibu post partum di Wilayah Kerja Puskesmas Panjang Bandar Lampung Tahun 2021.Metode jenis penelitian kuantitatif, desain penelitian metode pra Eksperimental dengan pendekatan One group pretest – posttest design, objek penelitian adalah pengaruh pemberian kompres daun kubis dingin terhadap pembengkakan payudara pada ibu post partum. Analisa data menggunakan univariat, bivariat uji t-tes dependen. Rata-rata pembengkakan payudara ibu post partum sebelum diberi kompres kubis dingin dengan mean4,00 sesudah diberi kompres kubis dingin dengan mean 0,77.Kesimpulan ada pengaruh pemberian kompres daun kubis dingin terhadap pembengkakan payudara ibu post partum di wilayah kerja puskesmas panjang bandar lampung tahun 2021.Saran petugas kesehatan agar dapat memberikan penyuluhan dan informasi yang baik tentang manfaat pengobatan non farmakologi dalam menangani masalah pembengkakan payudara pada ibu post partum, terutama bagi ibu dengan primipara dimana ibu tersebut belum memahami secara benar tentang cara pemberian ASI baik bagi ibu primipara untuk menghindari terjadinya bendungan ASI.Kata Kunci : Kompres Daun Kubis Dingin, Pembengkakan Payudara, Ibu Post Partum